PREFERRED WORD CHOICE: VARIATION OF TRANSLATIONS IN SUNDANESE QUR’ANIC TRANSLATION AND TAFSIR - Irma Riyani (Qur’anic and Tafsir studies Programme at Ushuluddin Faculty, 2022)
Translating the Qur’an into other languages is an urgent task following the spread of Islam not only to Arabic-speaking countries but also all over the world including Indonesia. The purpose of this article is to examine the process of the Qur’anic translation in the Sundanese Qur’anic translation and tafsir. This article investigates various preferred words choices by ulama in four Sundanese Translation and Tafsir namely: Qur’an Miwah Terjemah Dina Basa Sunda (QMTDBS, hereafter) published by the team members of West Java Ministry of Religious Affairs in 2005; 2) Tafsir Al Qur’an Basa Sunda (TQBS, hereafter), also published by West Java Ministry of Religious Affairs in 1981, 3) Tafsir Ayat Suci Lenyepaneun (TASL, hereafter); and 4) Roudhatul Irfan (RI, hereafter) written by K.H. Ahmad Sanoesi. Special attention is directed to investigating three aspects namely: 1) The procedure of using plural forms; 2) The usage of language levels; and 3) The preference of word choices for the translation of the same Arabic word. This research employs a qualitative method with content analysis of the text of Sundanese tafsir from different eras to accommodate the use of the Sundanese language in the changing society. The philological analysis also utilizes to scrutinize different word–by–word translations in these three texts. This research shows that: (1) There are differences in using plural forms from the source language into the targeted language in these Sundanese tafsir. For QMTDBS, they mostly eschewed the plural structure systematized in the Sundanese language. To our analysis, the shifting usage of the first aspect (1-plural) related to formulating the simple translation (uncomplicated) by eliminating one of the plural forms. The second aspect (2- language level) from coarse/refined to more refine language is associated with the changing society in Sundanese. The Qur’an which is positioned as sacred text represented high society and therefore uses more refined language. The third category (3) of various dictions usage is connected to territorial and context conventions which certainly influence the meaning-making of the translation process. Some Sundanese-translated words may not represent the equivalent meaning of the source language and it becomes one of the limitations in the translation process.